Core values and principles of general practice and family medicine: perspectives of German GP residents—a cross-sectional study - Dreher, Andreas Christian; Ko, Jonathan; Becker, Christine; Bischoff, Martina; Förster, Christian; Jähnig, Tanja; Stengel, Sandra; Altiner, Attila; Schwill, Simon (Frontiers in Medicine, 2025)
BackgroundThe core values and principles of general practice (GP) and family medicine (FM) have been described by various international scientific societies, including the World Organization of National Colleges, Academies, and Academic Associations of General Practitioners/Family Physicians (WONCA). These values and principles, such as continuity of care, a bio-psycho-social approach, and hermeneutic case understanding, are also integrated into FM training programs. The aim of this study was to investigate the knowledge and perspectives of FM trainees regarding the core values and principles of FM.MethodsIn a cross-sectional study, new participants of the postgraduate FM training program KWBW Verbundweiterbildung plus© were asked to complete a self-developed questionnaire on their educational experiences, attitudes toward, and knowledge of core values in GP/FM. Specifically, participants were asked to identify the core values and principles associated with GP/FM. Qualitative analysis was used to explore the answers. Additionally, participants were required to define a set of core values, which were then analyzed semi-quantitatively and rated as correct, semi-correct, wrong, or unknown.ResultsOut of a total of n = 303 trainees, n = 250 completed the questionnaire. The majority (n = 194) were in their third year of training. A third of the participants reported having studied core values in the past. The participants identified several core values and principles associated with GP/FM. The practical relevance and confirmation of becoming an FM doctor were well-evaluated.ConclusionThe study identified deficits in the active and passive knowledge of GP/FM core values among GP residents. An educational compact intervention about GP/GM core principles and values proved successful in its realization and implementation. To become a reflective practitioner in FM, GP residents must engage in self-reflection on evidence-based medicine, attitudes, core values, and principles. Therefore, core values should be addressed at the beginning of FM training and constantly referred to within the longitudinal curriculum. Family physicians should be continuously empowered to explicitly reflect on and discuss the core principles that shape their professional identity.